2019
DOI: 10.3390/su11174744
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Diverse Expectations of Stakeholders in Industrial Land Redevelopment Projects in China: The Case of Shanghai

Abstract: In China, while large-scale industrial land redevelopment has played a significant role in promoting economic growth, it has also triggered a series of unsustainable problems. To date, few studies have explored the expectations of stakeholders in industrial redevelopment projects in China. Gaining an in-depth understanding of the diverse expectations among core stakeholders is an essential step towards realizing social sustainability. This study aims to analyze these diverse expectations in industrial land red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…This approach is seen to be necessary to achieve consensus and thus is widely adopted in Western countries. Drawing on this idea, a good participatory mechanism on the basis of a profound understanding of various stakeholders in China’s complex social and economic system is necessary [ 10 , 53 ].…”
Section: Review Of Existing Research In Decision-making and Stakehmentioning
confidence: 99%
See 3 more Smart Citations
“…This approach is seen to be necessary to achieve consensus and thus is widely adopted in Western countries. Drawing on this idea, a good participatory mechanism on the basis of a profound understanding of various stakeholders in China’s complex social and economic system is necessary [ 10 , 53 ].…”
Section: Review Of Existing Research In Decision-making and Stakehmentioning
confidence: 99%
“…The majority of industrial factories located in the urban interior were moved to the edge of the city or closed, leaving a large number of vacant, inefficiently utilized industrial land plots and buildings [ 9 ]. There are two main approaches to the reuse of industrial space: adaptive reuse and industrial land redevelopment (ILR) [ 9 , 10 , 11 ]. Adaptive reuse refers to partially or completely converting the functions of the buildings on industrial site through appropriate renovation without changing the main building structure [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the affected residents in rehabilitation projects do not move out of the old neighborhoods, the rehabilitation of their neighborhoods and dwellings are their core interests (Zhuang, 2017). Another research carried out in Shanghai by He et al in 2019 revealed that initial expectation in a transformation project is "economic benefits for governments and other stakeholders" (He et al, 2019).…”
Section: Stakeholder Expectationsmentioning
confidence: 99%